Genetic and Epigenetic Determinants in Autoinflammatory Diseases - Álvarez-Errico, Damiana; Vento-Tormo, Roser; Ballestar, Esteban (Frontiers in Immunology, 2017)
The concept of autoinflammation has evolved over the past 20 years, beginning with the discovery that mutations in the Mediterranean fever (MEFV) gene were causative of Familial Mediterranean Fever (FMF). Currently, autoinflammatory diseases comprise a wide range of disorders with the common features of recurrent fever attacks, prevalence of hyperreactive innate immune cells, and signs of inflammation that can be systemic or organ-specific in the absence of pathogenic infection of autoimmunity. Innate immune cells from the myeloid compartment are the main effectors of uncontrolled inflammation that is caused in great extent by the overproduction of inflammatory cytokines such as IL-1 and IL-18. Defects in several signaling pathways that control innate immune defense, particularly the hyperreactivity of one or more inflammasomes, are at the core of pathologic autoinflammatory phenotypes. Although many of the autoinflammatory syndromes are known to be monogenic, some of them are genetically complex and are impacted by environmental factors. Recently, epigenetic dysregulation has surfaced as an additional contributor to pathogenesis. In the present review, we discuss data that is currently available to describe the contribution of epigenetic mechanisms in autoinflammatory diseases.